Analysis of Anemia Accompanied by Postpartum Bleeding Due to Uterine Atonia in Pregnant Women at Dr. Hospital. Pringadi Medan - Juli Yosa Mega (Formosa Publisher, 2023)
The research was carried out from February to March 2022 at RSUD Dr. Pirngadi Medan. The research sample was obtained by collecting secondary data in the form of medical records of pregnant women from 2017 to 2021. The aim of this study was to determine the number of cases of pregnant women suffering from anemia, the number of cases of women experiencing postpartum bleeding, the number of pregnant women experiencing anemia accompanied by bleeding. Postpartum caused by uterine atony. Using Unvariate and Bivariate Analysis, it was found that 68.0% of cases of pregnant women suffering from anemia were accompanied by postpartum bleeding (34 pregnant women); Postpartum hemorrhage caused by uterine atony was 38.0% (19 pregnant women); Meanwhile, 52.9% of pregnant women suffering from anemia accompanied by postpartum bleeding caused by uterine atony were found (18 pregnant women). The results of the analysis show a significant relationship between anemia in pregnant women and postpartum bleeding which is caused by uterine atony.